The contained litigation and exacerbated litigation in the Special Federal Civil Courts (Revista do Tribunal Regional Federal da 3ª Região, 2013)
The installation of the Special Federal Courts was accompanied by great satisfaction on the part of representatives of the Judiciary, especially in view of the so-called contained demand, that is, the unanticipated demand that would surprise enthusiasts for the expansion of the summary procedure to the federal court, thus reinforcing the relevance and urgency of creating such institutions. In the year that marks the tenth anniversary of the creation of the Special Federal Courts, the statistics of the São Paulo Special Court are astonishing, even for the megalopolis parameters that accompany the figures for the country's largest city. Despite the development of new techniques and the optimization of the management of similar cases, such as “batch” decisions, the JEF - SP still has 95,612 cases in progress at the present time (March 2012). Hence the need to discuss the success and growth of such a prominent institution in the Federal Judiciary, since the proclaimed and celebrated speed - which is a guideline of the JEFs' summary rite - has faced the obstacle of too many lawsuits, and - borrowing the expressions presented by Alexandre Freitas Câmara - the litigiousness initially contained has been transformed into exacerbated litigiousness to the point of compromising the execution of the goal of effective delivery of justice. The aim of this study is to explore the hermeneutic vectors that color this “special procedure”, in order to discourage the distribution of reckless demands, repetitive of settled theses or without the regular action of the Public Administration in the pre-procedural sphere.
Keywords: federal special courts; contained litigiousness; exacerbated litigiousness; structure; capillarization; harmonization with principles